Real-world data for monitoring antimicrobial resistance to urinary tract infection pathogens - A. A. Tsapkova; L. V. Mikhailova; S. V. Korenev; N. O. Kryukova; V. V. Rafalskiy (Реальная клиническая практика: данные и доказательства)
Relevance. The main treatment option for urinary tract infections is antimicrobials, which are selected empirically accord ing to local epidemiologic data. In recent years, a new source of data on antimicrobial resistance, which is based on real-world data (RWD) analysis.Objective. To study the distribution and structure of antimicrobial resistance of urinary infection pathogens in the Kalinin grad region according to RWD.Methods. The results of bacteriological studies on urine samples collected from inhabitants of the Kaliningrad region, which were performed in the INVITRO laboratory, were analyzed. The total number of bacteriologic studies in 2020 was 2251, in 2021–2765, in 2022–2544 and in 2023–2373 samples. Urine samples were collected from the outpatient clinic.Results. The study population was predominantly female (80.0 % to 89.9 %). The suspected causative agent was detected in 26.8 % — 29.3 % of patients. The most frequently isolated pathogen was E. coli (58.7 %–63.1 %). Other bacteria of the order Enterobacterales were isolated much less frequently: Klebsiella pneumoniae (6.4 %–9.7 %), Enterobacter spp. (0.9 %–2.4 %), Proteus spp. (0.3 %–2.9 %), and Pseudomonas aeruginosa (0.7 %–3.7 %). Among Gram-positive bacteria, Enterococci (6.3 %–7.8 %), Streptococcus agalactiae (1.6 %–3.6 %), and Staphylococcus saprophyticus (1.4 %–2.8 %) were most frequently isolated. Growth of resistance to almost all antimicrobial agents was noted. At the same time, fosfomycin (2.9 % of strains are resistant), nitrofurantoin (4.3 %), and amikacin (4.0 %) remain the most active E. coli-resistant drugs.Conclusion. The use of RWD to assess local antimicrobial resistance can be a valuable source of information, reflecting the true picture of antimicrobial resistance in a certain region and complementing the available information provided by other methods.